Regional Behavior of Airspaces During Positive Pressure Reduction Assessed by Synchrotron Radiation Computed Tomography - Scaramuzzo, Gaetano; Broche, Ludovic; Pellegrini, Mariangela; Porra, Liisa; Derosa, Savino; Tannoia, Angela Principia; Marzullo, Andrea; Borges, Joao Batista; Bayat, Sam; Bravin, Alberto; Larsson, Anders; Perchiazzi, Gaetano (Frontiers in Physiology, 2019)
INTRODUCTION: The mechanisms of lung inflation and deflation are only partially known. Ventilatory strategies to support lung function rely upon the idea that lung alveoli are isotropic balloons that progressively inflate or deflate and that lung pressure/volume curves derive only by the interplay of critical opening pressures, critical closing pressures, lung history and position of alveoli inside the lung. This notion has been recently challenged by subpleural microscopy, magnetic resonance and computed tomography. Phase-Contrast Synchrotron Radiation Computed Tomography (PC-SRCT) can yield in-vivo images at resolutions higher than conventional CT. OBJECTIVES: We aimed to assess the numerosity (ASden) and the extension of the surface of airspaces (ASext) in healthy conditions at different volumes, during stepwise lung deflation, in concentric regions of the lung. METHODS: The study was conducted in seven anesthetized New Zealand rabbits. They underwent PC-SRCT scans (resolution of 47.7 μm) of the lung at five decreasing positive end-expiratory pressure (PEEP) levels of 12, 9, 6, 3 and 0 cmH2O during end-expiratory holds. Three concentric regions-of-interest (ROI) of the lung were studied: subpleural, mantellar and core. The images were enhanced by phase contrast algorithms. ASden and ASext were computed by using the Image Processing Toolbox for MatLab. Statistical tests were used to assess any significant difference determined by PEEP or ROI on ASden and ASext. RESULTS: When reducing PEEP, in each ROI the ASden significantly decreased. Conversely, ASext variation was not significant except for the core ROI. In the latter, the angular coefficient of the regression line was significantly low. CONCLUSIONS: The main mechanism behind the decrease in lung volume at PEEP reduction is derecruitment. In our study involving lung regions laying on isogravitational planes and thus equally influenced by gravitational forces, airspace numerosity and extension of surface depend on the local mechanical properties of the lung.